Double-phase culture medium and growth regulators in the micropropagation of blackberries - Amanda, Islaine; Biasi, Luiz Antonio (Comunicata Scientiae, 2022)
Micropropagation is a technique that consists of producing disease-free and genetically uniform in vitro plants, which are produced in a shorter period of time than conventional propagation methods. The purpose of this study was to evaluate the effect of the consistency of the culture medium and the concentrations of BAP on the multiplication of sprouts, and concentrations of IBA on in vitro rooting of the Ébano and Tupy blackberry cultivars. The experiments were divided into three parts: In the first stage, culture media with solid, liquid, and double-phase texture were evaluated aiming at selecting the best culture medium in relation to quantity and quality of the sprouts. In the second stage, BAP concentrations were analyzed aiming at increasing the quantity of sprouts. In the third stage, IBA concentrations were evaluated aiming at optimizing root formation in the cultivars. The double-phase and liquid culture did not differ in the number of sprouts and leaves per explant and length of sprouts. The highest multiplication of sprouts on double-phase medium occurred with 5 μM L-1 BAP. Rooting was stimulated with the use of IBA and the best concentration was estimated at 1.1 μM IBA. The multiplication of Ébano and Tupy cultivars can be carried out in double-phase MS medium with 5 μM L-1 BAP and rooting in MS medium with 1.1 μM L-1 IBA.